Molecular-dynamic calculation of the relaxation of the electron energy distribution function in a plasma - David, N; Hooker, S (2003)
A molecular-dynamic (MD) code for calculating the relaxation of an arbitrary electron energy distribution in a plasma was described. The MD approach provided a more fundamental set of equations, with fewer assumptions. The accuracy of the MD approach was proved by comparing its results with the Monte Carlo and Fokker-Planck codes using a set of plasma parameters for which the Fokker-Planck calculation gave incorrect results. Calculating energy relaxation in plasmas proved important for the understanding of the operation of new types of short-wavelength lasers based on optical field ionization.